Analisis Implementasi Pelaksanaan E-Court di Pengadilan Agama - Piousty Hasna Arifany (Jurnal Riset Hukum Keluarga Islam, 2021)
Abstract. The research in this thesis is a type of content analysis and descriptive analysis. The data used in this study is primary data, namely interviews and secondary legal materials in the form of Perma No. 1 of 2019 concerning online case administration and the Letter of the Directorate General of the Religious Courts Agency, No. 5374/DJA/HM.01/X/2019. While the approach that the author uses is qualitative and normative-empirical. The author uses data collection techniques Literature Study, observation, interviews, and documentation. In the Letter of the Directorate General of the Religious Courts Agency, No. 5374/DJA/HM.01/X/2019 it has been explained that all Courts of First and Appeals within the Religious Courts immediately implement the e-court system as a follow-up to PERMA No. 1 of 2019. At the Bandung Religious Court, the e-court itself has been implemented since 2019, but the use of this e-court is deemed not optimal, during the COVID-19 pandemic situation, e-court can be a solution for litigation online in order to minimize crowds. The results of this study indicate that there are factors that hinder the implementation of e-court at the Bandung Religious Court. Abstrak. Penelitian ini bertujuan menganalisis kesesuaian implementasi pelaksanaan peradilan melalui e-court di Pengadilan agama Bandung dengan Perma No 1 Tahun 2019 Tentang Administrasi perkara secara online dan Surat Direktorat Jenderal Badan Peradilan Agama, No 5374/DJA/HM.01/X/2019. Penelitian ini bersifat normatif empiris. Dianalisis secara deskriptif. Data diperoleh melalui studi Pustaka, observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi pelaksanaan Perma No 1 Tahun 2019 Tentang Administrasi perkara secara online dan Surat Direktorat Jenderal Badan Peradilan Agama, No 5374/DJA/HM.01/X/2019 telah dilaksanakan sejak tahun 2019. Namun dalam pelaksanaannya belum efektif akibat literasi masyarakat terkait e-court masih rendah.